2008
DOI: 10.1111/j.1468-0394.2008.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of static and 50 Hz electric field effects on tissues by using a hybrid genetic algorithm and neural network

Abstract: The effects of electric fields on tissue are the main subject of many investigations. The importance of this subject comes from the electrical properties of the cell membrane and its sensitivity to changes in electrical conditions. Permeability of membranes to various ions can change by the effect of an electric field depending on their conductivity. The performances of cells and tissues change due to differences between the membrane's permeability to various ions and molecules. The aim of this study was to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The backpropagation learning algorithm is the most preferred method for training of the FNNs (Hardalaç & Güler, ; Jackowski & Wozniak, ; Pazera, Buciakowski, Witczak, & Mrugalski, ). Determination of the learning parameters (LPs), which are learning coefficients and momentum coefficients in backpropagation learning algorithm, is another major problem that affects on the performance of the network so the FNN applications have shown that a low value of the LPs decrease learning speed while a high value of the LPs increases the learning speed but may also result in oscillations which lead to no learning at all (Kandil, Khorasani, Patel, & Sood, ).…”
Section: Introductionmentioning
confidence: 99%
“…The backpropagation learning algorithm is the most preferred method for training of the FNNs (Hardalaç & Güler, ; Jackowski & Wozniak, ; Pazera, Buciakowski, Witczak, & Mrugalski, ). Determination of the learning parameters (LPs), which are learning coefficients and momentum coefficients in backpropagation learning algorithm, is another major problem that affects on the performance of the network so the FNN applications have shown that a low value of the LPs decrease learning speed while a high value of the LPs increases the learning speed but may also result in oscillations which lead to no learning at all (Kandil, Khorasani, Patel, & Sood, ).…”
Section: Introductionmentioning
confidence: 99%
“…Oh et al (2006) established sub-DFCIs (daily financial condition indicators) for various daily financial variables using an ANN and used the DFCI for the Korean financial market as an empirical case study. Hardalaç and Güler (2008) examined static and 50 Hz electric field effects on tissues and found that the prediction of the hybrid genetic algorithm and neural network approach was on average 99.25-99.99%. In terms of flooding, Campolo et al (1999) developed a neural network model to analyze and forecast the behaviour of the Tagliamento River in Italy during heavy rain periods.…”
Section: Introductionmentioning
confidence: 99%